Improved Transient-Based Overmodulation Method for Increased Torque Capability of Direct Torque Control with Constant Torque-Switching Regulator of Induction Machines - Alsofyani, Ibrahim Mohd; Lee, Kyo Beum (IEEE Transactions on Power Electronics, 2020)
In this article, a simple overmodulation method is proposed for achieving fast direct torque control with a constant torque-switching controller (CTSR-DTC) in induction machines. The conventional overmodulation method applied to CTSR-DTC focuses on attaining and maintaining the voltage vector with the largest tangential component to the locus of the stator flux. The selected voltage vector is held during the transient state and fed into the switching table. Nevertheless, unlike a classical DTC, the CTSR activates both zero- and active-voltage vectors owing to the nature of its operation. As a result, the optimized active voltage during an overmodulation cannot be maintained throughout the complete torque transient owing to an interruption by the zero-voltage vectors. To overcome this problem, the proposed method modifies the CTSR output to eliminate the zero-voltage vectors only during a transient state. Consequently, a full exploitation of the overmodulation is achieved, and hence an excellent torque dynamic response can be obtained when torque is demanded. Simulation and experimental results are provided to validate the effectiveness of the proposed overmodulation strategy.
Keywords: Direct torque control; Fast torque response; Induction machines; Overmodulation; Switching controllers; Switching regulator; Tangential components; Zero voltage vectors; Direct torque control (DTC); fast torque response; induction motor; overmodulation; torque control